2017
DOI: 10.1002/lary.27011
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis of induction chemotherapy as a selection marker for chemoradiation in the head and neck

Abstract: Objective Many trials incorporate induction chemotherapy (IC) in selecting for organ preservation in head and neck squamous cell carcinomas (HNSCC). However, few studies examine IC response in predicting for chemoradiation therapy (CRT) response. This meta‐analysis aims to determine the predictive accuracy of IC for subsequent response to CRT and overall survival (OS). Data sources Medline, EMBASE, Cochrane register. Methods A systematic search identified studies from database inception to October 2016 that us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Most induction chemotherapy studies were designed prior to the widespread incorporation of p16 testing and stratification into prospective studies of HNSCC. Given the improved prognosis related to HPV initiated HNSCC, interest in induction therapy has primarily been related to the idea of chemoselectionwith a goal toward treatment de-escalation [9]. ECOG 1308 demonstrated the feasibility of such a schema, but whether induction chemotherapy need be part of future deescalation regimens remains controversial and its use of cetuximab, which has been shown to be an inferior radiosensitizer to cisplatin, make this an unlikely platform to move forward [10,11].…”
Section: Induction Chemotherapy In Non-surgical Managementmentioning
confidence: 99%
“…Most induction chemotherapy studies were designed prior to the widespread incorporation of p16 testing and stratification into prospective studies of HNSCC. Given the improved prognosis related to HPV initiated HNSCC, interest in induction therapy has primarily been related to the idea of chemoselectionwith a goal toward treatment de-escalation [9]. ECOG 1308 demonstrated the feasibility of such a schema, but whether induction chemotherapy need be part of future deescalation regimens remains controversial and its use of cetuximab, which has been shown to be an inferior radiosensitizer to cisplatin, make this an unlikely platform to move forward [10,11].…”
Section: Induction Chemotherapy In Non-surgical Managementmentioning
confidence: 99%
“…Patients with at least a partial response to IC demonstrate improved survival, whereas patients with no response or progression during IC demonstrate poor prognoses. 10,21 Despite this utility, IC is not routinely utilized in the management of SNSCC. The purpose of this study was to analyze the National Cancer Database (NCDB), a nationwide cohort with a large number of SNSCC patients, to better understand which management strategies are being used.…”
mentioning
confidence: 99%
“…ICT also was a predictor of survival for locally advanced SCCHN. A recent meta-analysis study showed the ICT responders had better survival than nonresponders [28]. Moreover, a phase II study demonstrated that responders after one cycle of split-dose TPF ICT were a survival predictor for oral and oropharyngeal squamous cell carcinoma (OPSCC) [29].…”
Section: Discussionmentioning
confidence: 99%